Direito e Inovação: o novo Marco Legal de Ciência, Tecnologia e Inovação e a personalidade jurídica para os Núcleos de Inovação Tecnológica - Ricardo Santiago Silva de Gouvêa Ferreira (2017)
The importance and influence of Law on scientific research and innovation environments and the analysis of the new legal framework for innovation, including Constitutional Amendment no. 85 and Decree n. 9.283/18 are the background for the study of the possibility of the Technology Transfer Office to constitute itself with an own legal personality. The institutionalization of NITs (TTO) as a legal entity under private law, structured outside the hierarchy of the public institution to which it refers, is an explicit prediction of the new legislation and constitutes the main object of the research, as it can give better governance, more autonomy and better results. The new Legal Framework for Innovation significantly increased the competence for the performance of NITs (TTO), and thus, it is indispensable that this structure be endowed with greater managerial, financial and governance autonomy. In fact, the new legislation creates multiple possibilities for interaction between diverse sectors of society, and the NIT will be responsible for accommodating the interests of those involved, by making good and strategic use of the new legal tools. Given its greater autonomy, since it is constituted with its own legal personality, as a non-profit private entity, it will be able to use the skills necessary to the challenge that is presented.